Characterization of a prothrombotic phenotype using thrombin generation and thrombin activity in cirrhosis and portal hypertension. Issue 222 (February 2023) - Königsbrügge, Oliver; Scheiner, Bernhard; Simbrunner, Benedikt; Semmler, Georg; Quehenberger, Peter; Pabinger-Fasching, Ingrid; Trauner, Michael; Mandorfer, Mattias; Lisman, Ton; Ay, Cihan; Reiberger, Thomas
Abstract: Background: Patients with advanced chronic liver disease (ACLD) may develop a prothrombotic phenotype that seems to be more pronounced with more severe liver dysfunction. An imbalance of endogenous pro- and anticoagulants is not fully captured by routine coagulation assays. Methods: In a cohort of ACLD patients undergoing hepatic venous pressure gradient (HVPG) measurement, we assessed thrombin generation (TGA) using two commercially available assays (Technothrombin and Thrombinoscope) with and without addition of soluble thrombomodulin (TM), as well as thrombin activity, alongside a panel of coagulation parameters. Results: The cohort encompassed 37 patients (median age 55.3 years, mean HVPG 16 ± 5 mm Hg). In the TM-modified Thrombinoscope TGA, the endogenous thrombin generation potential (ETP) was significantly increased in Child-Pugh-Score (CPS) B/C patients (N = 23, 62 %) compared to CPS A patients (N = 14, 38 %) (ETP: 546 nM∗min (443–696) vs. 404 nM∗min (289–573), p = 0.028). Using the Technothrombin TGA without TM, patients with CPS B/C had decreased ETP compared to CPS A patients (ETP: 2792 ± 1336 nM∗min vs. 5040 ± 816 nM∗min, p < 0.001) and with addition of TM (final concentration: 5 nM; ETP: 2545 ± 1327 nM∗min vs. 4824 ± 929 nM∗min, p < 0.001). Thrombin activity levels were 0.6pM in median (0.2–1.6pM) and above the level of detectability (0.10pM) in 94.6 % of patients but were not correlated to severity of cirrhosis (CPS A 0.7pM vs CPS B/C 0.4pM, p = 0.377) nor to parameters of TGA. Conclusion: Thrombin plasma levels are elevated in liver disease patients without apparent correlation to TGA or severity of cirrhosis. TGAs can be modified with TM to enable protein C-dependent anticoagulation, but result in differences with regard to severity of liver disease. Highlights: Patients with advanced liver disease have an increased risk of thrombosis and bleeding. Thrombin generation (TG) increases with liver disease severity. TM-modified TG elucidates the hemostatic disbalance in liver disease. Thrombin plasma levels are increased in liver disease patients.